Introduction. (August 2015) - Evans, Brad; Tester, Keith
This special issue of Thesis Eleven has been published to mark the 70th anniversary of the bombing of Hiroshima and Nagasaki. The concern is to think about what the bombings mean today and how their challenge can be confronted across social and cultural thought and action. The question running through this special issue is: What do the bombings of Hiroshima and Nagasaki mean for us today?